Consensus recommendations for resistance testing in the management of chronic hepatitis C virus infection: Public Health England HCV Resistance Group. Issue 6 (December 2019) - Bradshaw, Daniel; Mbisa, Jean L; Geretti, Anna Maria; Healy, Brendan J; Cooke, Graham S; Foster, Graham R; Thomson, Emma C; McLauchlan, John; Agarwal, Kosh; Sabin, Caroline; Mutimer, David; Moss, Peter; et al.
Highlights: Consensus view from Public Health England's HCV Resistance Group. Review providing guidance on when and how to perform HCV resistance testing, and interpretation of results. Includes five key scenarios where HCV resistance testing is recommended in the UK and other similar settings. Abstract: The treatment of hepatitis C virus (HCV) infection has been revolutionised by the advent of oral, well-tolerated, direct acting antiviral therapies (DAA), with high cure rates. However, in some scenarios, HCV resistance to antiviral therapies may have an impact on treatment success. Public Health England's HCV Resistance Group was established to support clinicians treating people with HCV, where the issue of resistance may be a factor in clinical decision-making, and this review includes the Group's current recommendations on the use of HCV resistance testing. The authors describe the principles behind and approach to HCV resistance testing and consider evidence from in vitro studies, clinical trials and real world cohorts on the impact of HCV resistance on treatment outcomes for particular DAA regimens. Five scenarios are identified in the UK and similar settings, where, in the Group's opinion, resistance testing should be performed.